Resurrection of Pilumnus vinaceus A. Milne-Edwards, 1880 (Brachyura: Pilumnidae) using integrative evidence from molecular and morphology - Magalhães, Tatiana; Pantaleão, João A. F.; Mantelatto, Fernando L. (Zootaxa, 2021)
The hairy crab Pilumnus vinaceus A. Milne-Edwards, 1880, previously considered to be a junior synonym of Pilumnus dasypodus Kingsley, 1879 by Rathbun (1897) is here resurrected. Pilumnus vinaceus can be distinguished from the known western Atlantic species (including P. dasypodus) based on morphological characters and molecular markers. This action increases number of reported species of Pilumnus in the western Atlantic to nineteen.